2007
DOI: 10.1111/j.1471-8286.2007.01712.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite DNA primers for the endangered vermilion darter, Etheostoma chermocki, and cross‐species amplification in other darters (Percidae: Etheostoma)

Abstract: The endangered vermilion darter (Etheostoma chermocki) is endemic to the Black Warrior River system in the Mobile Basin in Alabama. Restoration and conservation of this species require an understanding of its population genetic structure, which can be characterized using microsatellite DNA. Nine microsatellite loci were developed; eight loci were polymorphic. Although observed heterozygosity was lower than expected heterozygosity in most polymorphic loci, only one locus showed significant deviation from Hardy–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Likewise, estimates of mean allelic richness of four other species of Etheostoma (Edberg 2009;Fluker et al 2010) are higher than in Yazoo darters (Table 2), though confidence intervals overlap with those of Yazoo darters from the Tallahatchie R. drainage, but not the Yocona R. drainage. Mean observed and expected heterozygosity of nine other species of Etheostoma (Tonnis 2006;Beneteau et al 2007;Khudamrongsawat et al 2007;Switzer et al 2008;Gabel et al 2008;Hudman et al 2008;Haponski et al 2009;Fluker et al 2010) show that for mean observed heterozygosity, confidence intervals overlap in all cases. However, mean expected heterozygosity was marginally lower for the Yocona R. drainage than the Tallahatchie R. drainage and other Etheostoma species and similar between other Etheostoma species and the Tallahatchie R. drainage with overlapping confidence intervals (Table 2).…”
Section: Genetic Diversity and Population Structurementioning
confidence: 89%
See 1 more Smart Citation
“…Likewise, estimates of mean allelic richness of four other species of Etheostoma (Edberg 2009;Fluker et al 2010) are higher than in Yazoo darters (Table 2), though confidence intervals overlap with those of Yazoo darters from the Tallahatchie R. drainage, but not the Yocona R. drainage. Mean observed and expected heterozygosity of nine other species of Etheostoma (Tonnis 2006;Beneteau et al 2007;Khudamrongsawat et al 2007;Switzer et al 2008;Gabel et al 2008;Hudman et al 2008;Haponski et al 2009;Fluker et al 2010) show that for mean observed heterozygosity, confidence intervals overlap in all cases. However, mean expected heterozygosity was marginally lower for the Yocona R. drainage than the Tallahatchie R. drainage and other Etheostoma species and similar between other Etheostoma species and the Tallahatchie R. drainage with overlapping confidence intervals (Table 2).…”
Section: Genetic Diversity and Population Structurementioning
confidence: 89%
“…Nuclear DNA was extracted using standard phenol-chloroform methods (Taggart et al 1992) and target sequences were amplified by PCR using 10 microsatellite primers developed for other species of Etheostoma: Esc 26b, Esc 18, Esc 187 (Etheostoma scotti) (Gabel et al 2008); Etsp 224, Etsp 227, Etsp 208, Etsp 219 (Etheostoma spectabile) ; Eche 010 (Etheostoma chermocki) (Khudamrongsawat et al 2007); and EosD 116, EosD 108 (Etheostoma osburni and E. variatum) (Switzer et al 2008). PCR reaction volume (11.5 ll) contained 109 reaction buffer (Genesee Scientific San Diego, CA), 50 mM MgCl 2 (Genesee Scientific San Diego, CA), 160 lM each dNTP, 1 lM each primer, and 1 U Taq polymerase (Apex Taq, Genesee Scientific San Diego, CA).…”
Section: Microsatellite Amplification and Allele Scoringmentioning
confidence: 99%
“…1). A total of nine sites were sampled for each species, with the exception of E. swaini in which collections occurred only at eight total sites (see Tables S1-S3 al., 2015), Etheostoma blennioides (Beneteau et al, 2007), E. caeruleum (Tonnis, 2006), E. chermocki (Khudamrongsawat et al, 2007), E. osburni (Switzer et al, 2008), E. scotti (Gabel et al, 2008), and Percina rex (Dutton et al, 2008). Each marker was reviewed for quality of amplification and polymorphism.…”
Section: Methodsmentioning
confidence: 99%
“…2000), Catonotus (Porter et al . 2002b), Oligocephalus (Tonnis 2006), and Ulocentra (Khudamrongsawat et al . 2007) provide a suite of molecular markers for conservation genetic and mating system studies in the Cherokee darter as well as in other species in the genera Percina, Ammocrypta, and Etheostoma .…”
Section: Pcr Conditions and Characterization Of Eight Microsatellite mentioning
confidence: 99%